2019
DOI: 10.1038/s41598-019-47403-1
|View full text |Cite
|
Sign up to set email alerts
|

Controlled generation of array beams of higher order orbital angular momentum and study of their frequency-doubling characteristics

Abstract: We report on a simple and compact experimental scheme to generate high-power, ultrafast, higher-order vortex-array beams. Simply by using a dielectric microlens-array (MLA) and a plano-convex lens, we have generated array-beams carrying the spatial property of the input beam. Considering the MLA as a 2D sinusoidal phase-grating, we have numerically calculated the intensity pattern of the array-beams in close agreement with the experimental results. Using vortex beams of order as high as l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
(29 reference statements)
1
2
0
Order By: Relevance
“…The nonlinear optical phenom ena are intensitydependent and the efficiency of the nonlin ear process decreases with decreasing the excitation intensity. In recent years, it has been shown that the efficiency of the second harmonic process decreases with increasing the vortex order (l) of the Gaussian vortex beam [46,47]. In a similar way, we have observed that the depth of zscan transmittance in 2PA as well as in 3PA decreased with increasing the vortex order (l) due to the decrease of peak intensity of the vortex beam as we discussed in figure 1.…”
Section: Discussionsupporting
confidence: 82%
“…The nonlinear optical phenom ena are intensitydependent and the efficiency of the nonlin ear process decreases with decreasing the excitation intensity. In recent years, it has been shown that the efficiency of the second harmonic process decreases with increasing the vortex order (l) of the Gaussian vortex beam [46,47]. In a similar way, we have observed that the depth of zscan transmittance in 2PA as well as in 3PA decreased with increasing the vortex order (l) due to the decrease of peak intensity of the vortex beam as we discussed in figure 1.…”
Section: Discussionsupporting
confidence: 82%
“…In addition to conventional optical vortices, multiple vortex modes with an array of spatially separated individual vortices [5] and optical vortex lattice (OVL) modes with multiple phase singularities on their wavefronts [6] have been proposed. OVL modes carry multiple OAM states and multiple dark cores can be used, allowing a significant increase in data capacity in communication systems [7] and the simultaneous trapping and manipulation of multiple particles [8].…”
Section: Introductionmentioning
confidence: 99%
“…TC represents the number of 2π phase cycles when the optical phase circles once the beam axis. The transverse cross-sections of the optical vortices are associated with helical phase wavefront 14,15 . In many cases, there is no connection between the polarization and phase vortex of light.…”
Section: All-optically Phase-induced Polarization Modulation By Meansmentioning
confidence: 99%